On the Edge of Uncertainty : Poverty Reduction in Latin America and the Caribbean during the Great Recession and Beyond - World Bank (World Bank, Washington, DC, 2017)
Strong poverty reduction in Latin America resumed with the growth rebound in 2010, as both moderate and extreme poor households benefitted from the recovery, accelerating poverty reduction to rates similar to those witnessed between 2003-2006 despite a 2.8 percent decline in Gross Domestic Product (GDP) per capita in Purchasing Power Parity (PPP) terms, poverty levels in Latin America (LAC) remained basically static during the great recession, as the poor were shielded from the economic crisis in some countries and continued to benefit from growth in others. In 2010, poverty reduction resumed sharply in Latin America, as household incomes were once again closely linked to economic growth at rates similar to pre-crisis years. Moderate poverty declined by almost 2.5 percentage points to reach 28 percent in 2010, while extreme poverty fell by more than 2 percentage points to reach 14 percent. As 2011 comes to a close, once again the global economy and Latin America are facing risks of yet another economic slowdown. Using household survey data from 2010 and selected labor market indicators through the third quarter of 2011, this note identifies some basic facts on the impact of the crisis and the recovery on the poor and explores their implications for poverty reduction in the region going forward.